Optimization of Pore Structures and Supercapacitor Properties of Carbon Aerogel Electrodes - Kim, Chang-Yeoul; Rum Jang, A.; Youn Cho, Kwang (Asian Journal of Chemistry, 2012)
In this study, the porous series of carbon aerogel (CA) by a magnesium acetate catalyst molar ratio, CA50, CA100, CA200 and CA500, were derived via the pyrolysis of resorcinol-formaldehyde (RF) aerogel. Pore structure analysis shows that a magnesium acetate ratio is increasing with decreasing a pore and particle size by FESEM. Surface area analysis is increasing with increasing a catalyst ratio by nitrogen adsorption/desorption analysis. The results show that BET surface area and specific capacitance increase with decreasing R/C ratio (molar ratio of resorcinol to catalyst). The BET surface area of carbon aerogel decreases from 763 m2/g for CA50 to 523 m2/g for CA500. The micropore volume are almost same for carbon aerogels, but the mesopore volume and specific surface area decreased with increasing R/C ratio, especially drastically decreased for CA500. The macropore volume decrease is not so high, about 0.3 cc/g from 2.3 cc/g for CA50 to 2.0 cc/g for CA500, indicating that CA500 is mainly comprised of macropores and micropores. To measure the real supercapacitance of carbon aerogels, we measured full-cell galvanostatic charge and discharge properties and cyclic voltammetry (CV) properties. The calculated capacitance of supercapacitors 24.5 F/g for CA50, 21.9 F/g for CA100, 11.3 F/g for CA200 and 4.5 F/g for CA500. We found that specific capacitance is increasing with increasinga surface area and large amount of mesopores.